The Clinical and Radiologic Outcomes of Early Loaded Implants After 5 Years of Service - ÖZKAN, YASEMİN; ASLAN, YILMAZ UMUT (QUINTESSENCE PUBLISHING CO INC, 2020)
Purpose: To evaluate the 5-year results of the clinical and radiographic outcomes of three types of early loaded implants. Materials and Methods: Seventy-five implants were placed in the posterior mandible or maxilla in 30 patients. Three types of implants (Straumann SLActive, Astra OsseoSpeed, and Thommen Implant System) were used. Definitive restorations were made after 8 weeks of implant placement. The radiographs were taken at the placement of the prosthesis, at 6 months, and at 1- and 5-year follow-ups. Clinical and radiologic data were evaluated for all types of implants. The Wilcoxon signed rank test, least significant differences, and Mann-Whitney U were used to test for statistically significant differences (P < .005). Results: Twenty-four patients and 62 implants were evaluated after 5 years. The mean marginal bone loss was 0.20 +/- 0.40 mm, 0.21 +/- 0.05 mm, and 0.25 +/- 0.36 mm after 1 year and 0.32 +/- 0.22 mm, 0.31 +/- 0.26 mm, and 0.42 +/- 0.36 mm after 5 years for the Straumann, Astra, and Thommen groups, respectively. After 5 years, the mean peri-implant probing depth level was 1.75 +/- 0.49 mm, 1.87 +/- 0.48 mm, and 1.92 +/- 0.57 mm for the Straumann, Astra, and Thommen groups, respectively. No peri-implantitis was detected after 5 years of loading. Conclusion: All groups of implants showed a stable peri-implant probing depth and marginal bone level. The survival rate was high and bone loss was low at 5 years; thus, early loading may be a useful procedure that allows reduction in treatment time.
Keywords: early loading; implant stability; marginal bone loss; RESONANCE FREQUENCY-ANALYSIS; SUBMERGED TITANIUM IMPLANTS; IMMEDIATE NON-OCCLUSAL; ACID-ETCHED IMPLANTS; MARGINAL BONE LOSS; DENTAL IMPLANTS; EXTRACTION SOCKETS; SLA IMPLANTS; POSTERIOR MAXILLA; CONTROLLED-TRIAL